Effectiveness of nitazoxanide in the treatment of COVID-19 related diarrhoea (Bangladesh Medical Journal Khulna, 2022)
Background: Diarrhoea is becoming one of the most prominent and troublesome manifestations in COVID-19 infection but no definitive treatment is available. So Nitazoxanide was used to see whether it can shorten the duration and sufferings form COVID-19 related diarrhoea.Objective: To see the efficacy of Nitazoxanide in decreasing frequency and improving the consistency of stool in COVID-19 related diarrhoea.Methods: This randomized comparative study was done in private chambers of medicine specialists in Khulna and patients admitted in corona dedicated hospital, Khulna from July 2020 to June 2021. 100 patients were enrolled in the study using Nitazoxanide & ORS (oral rehydration solution) in 50 patients and only ORS in another 50 patients. Decreased frequency and volume of stool at 24, 48 and 72 hours of both groups were compared.Results: After giving Nitazoxanide in diarrhoea of COVID-19 patients, improvement was in 90% patients at 24 hours: in 96% patients in 48 hours and in 98% cases at 72 hours. On the other hand, without Nitazoxanide improvement was found in 30%, 40% and 50% cases at 24, 48 and 72 hours respectively. So Nitazoxanide was effective (p